Portfolio management in new product development lessons from the leaders I - Cooper, Robert G.
Robert G. Cooper, Scott J. Edgett and Elko J. Kleinschmidt report how leading firms attempt to maximize the value of their R&D portfolios and achieve the right product balance and mix.
Effective portfolio management, project selection and resource allocation were deemed critical to new product success at 35 companies. However, virtually every company admitted having problems and considered the techniques it was using to be experimental.
A study of portfolio management practices in industry reveals three goals : maximizing the value of the portfolio, achieving the right balance and mix of projects, and linking the portfolio to the business's strategy. This first of two articles provides examples of portfolio methods used to achieve the first two goals. Maximizing the portfolio's value is achieved by means of various financial models, including the Expected Commercial Value method and the Productivity Index, which are outlined and critiqued. Scoring models are also used to maximize the value of the portfolio. Achieving a balanced portfolio is quite a different issue. involving the use of bubble diagrams and other visual models.
Keywords: Portfolio management